Liver Cancer Disparities in New York City: A Neighborhood View of Risk and Harm Reduction Factors - Kamath, Geetanjali R.; Taioli, Emanuela; N. Egorova, Natalia; Llovet, Josep M.; Perumalswami, Ponni V.; Weiss, Jeffrey J.; Schwartz, Myron; Ewala, Stanley; Bickell, Nina A. (Frontiers in Oncology, 2018)
Introduction: Liver cancer is the fastest increasing cancer in the US and is one of the leading causes of cancer-related death in New York City (NYC), with wide disparities among neighborhoods. The purpose of this cross-sectional study was to describe liver cancer incidence by neighborhood and examine its association with risk factors. This information can inform preventive and treatment interventions. Materials and Methods: Publicly available data were collected on adult NYC residents (n=6,407,022). Age-adjusted data on the outcome – liver and intrahepatic bile duct cancer – came from the New York State Cancer Registry (2007-2011 average annual incidence); and the NYC Vital Statistics Bureau (2015, mortality). Data on liver cancer risk factors (2012-2015) were sourced from the New York City Department of Health and Mental Hygiene (NYCDOHMH): 1) Community Health Survey, 2) A1C registry 3) NYC Health Department Hepatitis surveillance data. They included prevalence of obesity, diabetes, diabetic control, alcohol-related hospitalizations or ED visits, hepatitis B and C rates, hepatitis B vaccine coverage, and injecting drug use. Results: Liver cancer incidence in NYC was strongly associated with neighborhood poverty after adjusting for race/ethnicity (β=0.0217, p=0.013); and with infection risk scores (β=0.0389, 95%CI=0.0088-0.069, p=0.011), particularly in the poorest neighborhoods (β=0.1207, 95%CI=0.0147-0.2267, p=0.026). Some neighborhoods with high hepatitis rates do not have a proportionate number of hepatitis prevention services. Conclusions: High liver cancer incidence is strongly associated with infection risk factors in NYC. There are gaps in hepatitis prevention services like syringe exchange and vaccination that should be addressed. The role of alcohol and metabolic risk factors on liver cancer in NYC warrants further study.